An An Error Analysis in Translating Indonesian Text into English by Fourth Semester of the English Education Study Program at Nommensen HKBP University Medan - Aryo Hans Lumban Tobing; Lendawati Manurung; Pitriani Nababan; Inanti P. Diran (Journal of Language Education (JoLE), 2025)
This study examines the translation errors made by fourth-semester English Education students at HKBP Nommensen University Medan when translating expository texts from Indonesian into English. Employing a qualitative descriptive approach and the Surface Strategy Taxonomy by Dulay, Burt, and Krashen (1982), the research classifies errors into omission, addition, misformation, and misordering. Data were collected from student translation assignments.The purpose of this study is to identify the types and frequency of errors as well as the translation strategies students used, in order to understand the linguistic and contextual challenges they face. The findings revealed that misformation errors were the most dominant (75.82%), followed by addition and omission (each 10.48%), and misordering (3.22%). All 20 participants relied heavily on literal translation techniques, which often resulted in unnatural sentence structures and incorrect grammatical forms. This study highlights the need for more targeted grammar instruction, sentence restructuring exercises, and contextual vocabulary training. It contributes to the existing literature on translation errors in academic texts and offers practical insights for improving translation pedagogy and curriculum development in English education programs.